Pendekatan Kualitatif dalam Penelitian Tindakan: Sebuah Risalah dalam Pemanfaatan Pendekatan Kualitatif - Maulida, Maulida; Zamroni, Zamroni (IAINU Kebumen, 2023)
Action research is a research method conducted during the ongoing actions or activities in a particular step of a process with the aim of producing a better course of action in the subsequent steps. Action research that combines qualitative and quantitative approaches generally faces challenges in its implementation. Action research considers alternative research designs that directly address the considerations regarding the strengths and weaknesses of qualitative and quantitative data. Practitioners of action research often emphasize the use of quantitative data and its analysis because quantitative data is easily obtainable, measurable, and generalizable. This inclination tends to relegate qualitative research to a supplementary role in the implementation of action research. The advantage of the quantitative approach lies in its ability to measure reactions from a large number of individuals through a limited set of questions, facilitating comparisons and statistical calculations on aggregated data. This provides breadth and a set of findings that can be generalized. Conversely, the qualitative method specifically yields rich and detailed data about a limited number of individuals and cases. While not easily generalizable, the qualitative approach offers an in-depth understanding of the context and complexity of a phenomenon. Therefore, it is essential to strike a balance between these two approaches to gain a holistic understanding in action research.